Analisis Putusan Nomor 394/Pdt.G/2021 Pn Smg Hukum Terhadap Tidak Terpenuhinya Prestasi Dalam Kontrak Perusahaan Dalam Bidang Jasa Konstruksi Baja - Cahyaningsurya, Nabila Sahara; Marwiyah, Siti; Handayati, Nur; Sidarta, Dudik Djaja; Hartoyo, Hartoyo (UNES Law Review, 2023)
This study aims to analyze the settlement of defaults in steel construction services projects between PT Indotrans Construction, PT Bima Agung, and PT Duta Mas, which are discussed in Decision Number 394/Pdt.G/2021 PN Smg. The research method used is a normative legal research method with statutory, case conceptual, and qualitative analysis approaches. The results of the study show that Decision Number 394/Pdt.G/2021 PN Smg is in accordance with the principles of contract law. The legal consequences experienced by PT Bima Agung and PT Duta Mas Indah as the defendants who were declared in default by the panel of judges were required to pay for the losses suffered by the plaintiffs.